Fidelity of a human cell DNA replication complex. - Roberts, J D (1988)
We have measured the fidelity of bidirectional, semiconservative DNA synthesis by a human DNA replication complex in vitro. Replication was performed by extracts of HeLa cells in the presence of simian virus 40 (SV40) large tumor antigen by using a double-stranded phage M13mp2 DNA template containing the SV40 origin of replication and either of two different target sequences for scoring mutations in the lacZ alpha-complementation gene, which encodes the alpha region (specifying the amino-terminal portion) of beta-galactosidase. Replicative synthesis was substantially more accurate than synthesis by the human DNA polymerase alpha-DNA primase complex purified from HeLa cell extracts by immunoaffinity chromatography, suggesting that additional factors or activities in the extract may increase fidelity during bidirectional replication. However, by using a sensitive opal codon reversion assay, single-base substitution errors were readily detected in the replication products at frequencies significantly higher than estimated spontaneous mutation rates in vivo. These data suggest that additional fidelity factors may be present during chromosomal replication in vivo and/or that the fidelity of replication alone does not account for the low spontaneous mutation rates in eukaryotes.